Immigration Stress among Recent Latino Immigrants: The Protective Role of Social Support and Religious Social Capital. Issue 4 (19th May 2019) - Sanchez, Mariana; Diez, Stephanie; Fava, Nicole M.; Cyrus, Elena; Ravelo, Gira; Rojas, Patria; Li, Tan; Cano, Miguel Angel; De La Rosa, Mario
ABSTRACT: Religious institutions can be a source of support for recent Latino immigrants struggling to adjust to a new culture. For undocumented immigrants, who are often marginalized from other formal institutions, they may symbolize a place of refuge and hope through supportive social networks that mitigate common challenges such as social isolation and other forms of immigration stress. This cross-sectional study examined the impact of religious social capital and social support on immigration stress among documented and undocumented recent Latino immigrants ( N = 408). Religious social capital was associated with higher levels of social support, while social support was protective against immigration stress. Social support mediated associations between religious social capital and immigration stress, but only among undocumented immigrants. Findings suggest religious social capital may be a particularly useful resource for undocumented immigrants, aiding in the provision of social support and in decreasing levels of immigration stress. Future research directions and implications for culturally tailored service delivery are presented.